Patient perceptions and preferences about prostate fiducial markers and ultrasound motion monitoring procedures in radiation therapy treatment. Issue 1 (30th September 2020) - Brown, Amy; Pain, Tilley; Preston, Robyn
Abstract: Introduction: Patient experiences and preferences of image‐guidance procedures in prostate cancer radiotherapy are largely unknown. This study explored experiences and preferences of patients undergoing both fiducial marker (FM) insertion and Clarity ultrasound (US) procedures. Methods: A sequential explanatory mixed method approach was used. A questionnaire ( n = 40) ranked experiences from 0 to 10 (worst) in the domains of invasiveness; pain; physical discomfort; and psychological discomfort. Responses were analysed with descriptive and inferential statistics. Semi‐structured interviews ( n = 22) obtained further insights into their perspectives and preferences and were thematically analysed. Results: Perceptions of invasiveness varied with 46% reporting FMs more invasive than US and 49% the same for the two procedures. The mean score for FM was 3.6 and 2.1 for US. Mean scores for pain, physical and psychological discomfort were higher for FMs with 3.3, 3.2 and 2.9, respectively, and 1.1, 1.2 and 1.7 respectively for US, only pain achieved significance ( P < 0.05). Three themes emerged from the interviews: Expectations versus Experience; Preferences linked to Priorities; and Motivations. Eleven patients (50%) preferred US; however, 10 (45%) could not illicit a preference. Conclusion: Participants found both of the FM and US image‐guidance procedures tolerable and acceptable. Men's preference was elusive, suggesting a more rigorous preference methodology is required to understand preferences in this population. Abstract : Patient experiences and preferences of image‐guidance procedures in prostate cancer radiotherapy are largely unknown. This study explored experiences and preferences of patients undergoing both fiducial marker (FM) insertion and Clarity ultrasound (US) procedures. Men's preference was elusive, suggesting a more rigorous preference methodology is required to understand preferences in this population.